Bacterium, Fungus, and Virus Microorganisms for Energy Storage and Conversion. Issue 12 (21st October 2019) - Shen, Shenghui; Zhou, Rongfan; Li, Yahao; Liu, Bo; Pan, Guoxiang; Liu, Qi; Xiong, Qinqin; Wang, Xiuli; Xia, Xinhui; Tu, Jiangping
Abstract: Since rapidly increasing energy demands have aroused tremendous research activities on energy storage and conversion, microorganisms (e.g., bacteria, fungi, and viruses) have played significant roles in developing high‐performance electrodes due to their strong abilities of fast reproduction, biomineralization, gene modification, and self‐assembly. Recently, a large quantity of bacteria and fungi has been utilized as the precursors to produce heteroatom–doped carbons or as the biofactories and templates to biomineralize the metal ions to form carbon‐based composites. In addition, in virtue of easy genetic modification, nanoscale viruses with functional groups are directly used as biotemplates for the self‐assembly of the active materials. In this review, a detailed introduction on the microorganisms and their unique abilities as well as the mechanisms behind their operations are discussed. Moreover, recent progress on bacteria‐ and fungi‐derived carbon materials and their composites, as well as the virus‐templated bio‐materials as the electrodes in electrochemical fields, including batteries and electrocatalysts, are further summarized. Finally, challenges and perspectives on the development of the microorganism derivations in electrochemical fields are also provided. This review offers guidance for the rational design of advanced electrode materials from microorganisms and extend the energy systems from the man‐made to biofabrication. Abstract : Microorganisms (e.g., bacteria, fungi, and viruses) with the unique abilities of fast reproduction, biomineralization, gene modification, and self‐assembly have aroused tremendous attention in energy‐related fields. The recent progress of microorganisms and their derivatives for electrochemical storage and conversion devices is summarized with the emphasis on synthesis, nanostructure, morphology, synergistic effects, and the detailed electrochemical properties. Additionally, the relationship and mechanism of the gene modification, biomineralization, and self‐assembly behaviors of microorganisms are further studied.